2010
DOI: 10.5897/ajb09.1568
|View full text |Cite
|
Sign up to set email alerts
|

Protective role of interferon against cytotoxcicity induced by rabies virus in mice

Abstract: Rabies remains an important public health problem in the world due to uncontrolled enzootic rabies, lack of safe efficient vaccines and poor information on the risk of contracting rabies post animal exposure. The lethality and mutagenic potential of challenge virus standard (CVS) was evaluated in mice. Mice were intracerebrally infected (MIC) with low, medium and high viral LD 50 (MICLD 50 ). Mice were subjected to immunomodulation using interferon (IFNα-2a) pre-infection. The infected groups pretreated with I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
2
2
0
Order By: Relevance
“…The increased survival rate and reduced cytogenetic changes suggest that protection induced by interferon against rabies virus activity could be, at least partially, attributable to blockage of the replication of CVS strain of rabies virus. [12] Similar observation was reported from study involving monkeys infected with rabies virus when administered by repeated intramuscular administration of human leukocyte interferon beginning 24 h after infection. [7] Bosko Postic et al, showed simultaneous inoculation of interferon and street rabies in rabbit in opposite hind limbs decreased the mortality but interferon in vitro failed to neutralise rabies virus.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The increased survival rate and reduced cytogenetic changes suggest that protection induced by interferon against rabies virus activity could be, at least partially, attributable to blockage of the replication of CVS strain of rabies virus. [12] Similar observation was reported from study involving monkeys infected with rabies virus when administered by repeated intramuscular administration of human leukocyte interferon beginning 24 h after infection. [7] Bosko Postic et al, showed simultaneous inoculation of interferon and street rabies in rabbit in opposite hind limbs decreased the mortality but interferon in vitro failed to neutralise rabies virus.…”
Section: Discussionsupporting
confidence: 83%
“…The infected Swiss albino mice were observed for mortality upto 21 days. [12] The pre-exposure and post-exposure treatments of rhuIFN α-2a challenged with RV CVS were repeated in triplicate. All the infectious work was carried out in Biosafety level-2 cabinet.…”
Section: Pre-exposure and Post-exposure Treatmentsmentioning
confidence: 99%
“…Our results were similar to that reported by Tohamy et al, where pre treatment of mice with IFN, 24 h before infection delayed the onset of specific rabies signs [31]. Therefore, based on development of characteristic signs of illness in the pre-exposure and post-exposure groups, we speculated that priming with interferon in the pre-exposure group can lead to local production of cytokines and recruitment of lymphocytes.…”
Section: Discussionsupporting
confidence: 81%
“…However, the mechanism behind the reported protective activity of exogenous interferon is not clear. Recently Tohamy et al, demonstrated that pretreating rabies infected mice with interferon significantly reduced cytogenetic changes [31]. These reports formed the basis of the present study which is an attempt to investigate the role of recombinant human interferon alpha (rhIFN a-2A) on prognosis and expression of innate immunity cytokines during rabies infection.…”
Section: Introductionmentioning
confidence: 95%